2012
DOI: 10.1177/0269216312440606
|View full text |Cite
|
Sign up to set email alerts
|

The views of patients with severe chronic obstructive pulmonary disease on advance care planning: A qualitative study

Abstract: Considering advance care planning as a repeated process of discussion of prognosis, concerns and probable preferences for care would be more useful than encouraging binding advance decisions. Further research should assess the effectiveness of this approach. Local coordination of who is responsible for information provision is needed, and greater involvement of patients with COPD in management decisions as they arise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 22 publications
6
88
0
Order By: Relevance
“…An understanding of these issues has the potential to mitigate unwanted interventions, such as intubation and ventilation, and has been shown to reduce psychological stress for both patients and carers [93,94]. Despite the fact that chronic lung diseases, such as COPD, are a leading cause of mortality worldwide, the issue of advance care planning is often poorly addressed as part of their clinical management [95][96][97]. Advance care planning for people with end-stage cardiorespiratory disease is considered challenging, as the disease progression is often variable and gradual, hospitalisations are episodic, prognosis may be unclear and people may not recognise the seriousness of their condition [95].…”
Section: Advance Care Planningmentioning
confidence: 99%
“…An understanding of these issues has the potential to mitigate unwanted interventions, such as intubation and ventilation, and has been shown to reduce psychological stress for both patients and carers [93,94]. Despite the fact that chronic lung diseases, such as COPD, are a leading cause of mortality worldwide, the issue of advance care planning is often poorly addressed as part of their clinical management [95][96][97]. Advance care planning for people with end-stage cardiorespiratory disease is considered challenging, as the disease progression is often variable and gradual, hospitalisations are episodic, prognosis may be unclear and people may not recognise the seriousness of their condition [95].…”
Section: Advance Care Planningmentioning
confidence: 99%
“…Patients with COPD find it particularly difficult to make decisions in advance about ceilings of care [24] and even when they have had prior experience of interventions such as noninvasive ventilation they trust their doctor to make the right decision about its use in future in preference to making their own decision [25]. Nevertheless it is important that they are given the opportunity to discuss such issues.…”
mentioning
confidence: 99%
“…Providers may have concerns about their patients' perceptions of the ACP discussion and possibly unmasking patient anxiety or depression about end of life issues (Curtis & Patrick, 1997;Gott et al, 2009;Knauft, Nielsen, Engelberg, Patrick, & Curtis, 2005). These barriers are similar to those expressed by providers treating other chronic diseases (Gott et al, 2009;MacPherson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ACP discussions correlate with better health-care outcomes and satisfaction with care among various chronic disease populations such as chronic obstructive pulmonary disease (COPD) and diabetes. Patients with COPD report that ACP improves their health care and that the process of discussion regarding prognosis, treatment concerns, and preferences for care involved in ACP is valuable (Janssen, Engelberg, Wouters, & Curtis, 2012;MacPherson, Walshe, O'Donnell, & Vyas, 2012). Similarly, insulin-dependent diabetics have expressed a desire to discuss ADs (Toth, Gill, Godkin, & Lee, 1998).…”
Section: Introductionmentioning
confidence: 99%